Translators Talk about Themselves, Their Work and Their Profession: The Habitus of Translators of Russian Literature into Hebrew - Voinova, Tanya; Shlesinger, Miriam (TTR)

(untitled) (Association canadienne de traductologie, 2013)
In his discussion of the habitus of translators throughout history, Simeoni highlights the submissiveness and invisibility associated with their inferior position and with their tendency to assimilate and internalize these views of their professional activities. In keeping with recent reappraisals of this position, the present paper examines the ways in which translators of Russian literature into Hebrew, from the 1970s to now, present themselves, their work and their profession—and reflect on their habitus, their conduct in the system of Russian literature translation, and their practice. From the theories of Bourdieu and of Even-Zohar, we explore these self-representations, and find that rather than presenting themselves as invisible, passive and professionally indistinct, these translators make a point of announcing their presence as well as of emphasizing their work. While they adopt different models, they nevertheless share a repertoire and both a social and a professional habitus—one that is a prerequisite for entering the field of literary translation, and particularly the subfield of literary translation of Russian literature, and for operating successfully in these arenas. It is in this way that they achieve status in the culture, accumulate capital and construct their (distinctive) group identity. In addition, the discourse of Russian literary translators points to the dynamic nature of their system and helps push it towards the center of the polysystem of Hebrew translated literature.